A Primer on the Acute Management of Intravenous Extravasation Injuries for the Plastic Surgeon. Issue 4 (April 2018) - Maly, Connor; Fan, Kenneth L.; Rogers, Gary F.; Mitchell, Benjamin; Amling, June; Johnson, Kara; Welch, Laura; Oh, Albert K.; Chao, Jerry W.
Abstract : Intravenous therapy is a common practice among many specialties. Intravenous therapy extravasation is a potential complication to such therapy. Hospitals without a dedicated wound care team trained in these interventions will often default to plastic surgical consultation, making an understanding of available interventions essential to the initial evaluation and management of these injuries. The goal of this article was to provide plastic surgeons and health care providers with a general overview of the acute management of intravenous infiltration and extravasation injuries. Though the decision for surgical versus nonsurgical management is often a clear one for plastic surgeons, local interventions, and therapies are often indicated and under-utilized in the immediate postinfiltration period. Thorough knowledge of these interventions should be a basic requirement in the armamentarium of plastic surgery consultants.